2007
DOI: 10.1158/0008-5472.can-06-2964
|View full text |Cite
|
Sign up to set email alerts
|

Methylation-Independent Silencing of the Tumor Suppressor INK4b (p15) by CBFβ-SMMHC in Acute Myelogenous Leukemia with inv(16)

Abstract: The tumor suppressor gene INK4b (p15) is silenced by CpG island hypermethylation in most acute myelogenous leukemias (AML), and this epigenetic phenomenon can be reversed by treatment with hypomethylating agents. Thus far, it was not investigated whether INK4b is hypermethylated in all cytogenetic subtypes of AML. A comparison of levels of INK4b methylation in AML with the three most common cytogenetic alterations, inv(16), t(8;21), and t(15;17), revealed a strikingly low level of methylation in all leukemias … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…Previously, low RNA levels of p15 were reported in AML (Schwaller et al, 1997) which was also correlated with methylation of this gene (Matsuno et al, 2005). However, Markus et al (2007) reported silencing of p15 gene in AML even in the absence of methylation, suggesting other cellular mechanisms to be involved, but most importantly this pointed to the significance of this gene in the pathology of the AML disease. In this study a methylation frequency of 11% was seen in CML patients.…”
Section: Discussionmentioning
confidence: 95%
“…Previously, low RNA levels of p15 were reported in AML (Schwaller et al, 1997) which was also correlated with methylation of this gene (Matsuno et al, 2005). However, Markus et al (2007) reported silencing of p15 gene in AML even in the absence of methylation, suggesting other cellular mechanisms to be involved, but most importantly this pointed to the significance of this gene in the pathology of the AML disease. In this study a methylation frequency of 11% was seen in CML patients.…”
Section: Discussionmentioning
confidence: 95%
“…In this type of AML, the inversion (16) results in a fusion protein between the core binding factor (CBFβ) and the smooth myosin heavy chain gene (SMMHC). This chimeric transcription factor CBFβ-SMMHC binds directly to the promoter of p15INK4b and represses its expression (Markus et al, 2007). These results further emphasize an important role of p15INK4b silencing in leukemogenesis of the myeloid lineage, and suggest, that in the absence of a repressive epigenetic event, other mechanisms may result in inhibition of p15INK4b expression (Markus et al, 2007).…”
Section: Introductionmentioning
confidence: 82%
“…In the pediatric form of the disease, juvenile myelomonocytic leukemia (JMML), p15INK4b hypermethylation is found to be a less frequent, however, still significant event (17% of cases) (Hasegawa et al, 2005). With regards to cytogenetic abnormalities, p15INK4b methylation levels have been found to occur at higher frequencies in AML/MDS patients with an unfavorable karyotype (Wong et al, 2000;Galm et al, 2005;Shimamoto et al, 2005;Markus et al, 2007). Cases with unmethylated or low levels of hypermethylated p15INK4b were associated with normal karyotype or with those karyotypic abnormalities that are associated with a favorable prognosis (Wong et al, 2000;Markus et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A striking 80% of human leukemia and MDS cases have silenced expression of the CDKN2B locus that encodes the tumor suppressor p15Ink4b [2][3][4][5][6][7]. Nonetheless, the function of p15Ink4b in the disease development remains to be elucidated [8,9].…”
Section: Introductionmentioning
confidence: 99%